Relationship between Renal Function Status with Infected of Chronic Hepatitis B in Fallujah Teaching Hospital - Ali, Mohamed Fouad; Shaaban, Mohamed Madani; Atallah, Bilal Maher; Neda, Mustafa Ziad; Saleh, Omar Hamed (American Journal of Biology and Natural Sciences, 2025)
Hepatitis B virus (HBV) infection is a global health problem that affects many body systems, including the kidneys. This study aims to explore the relationship between renal function status and chronic HBV infection in patients at Fallujah Teaching Hospital, which contributes to improving the understanding of the impact of the disease on the renal system. Materials and methods: The study was conducted from 20th July to 25th September 2023 at Fallujah Teaching Hospital in Fallujah city in Iraq on two groups: patients with chronic hepatitis B, and a control group of healthy individuals. Blood samples were collected from the participants and tested for HBV detection test using RDT and ELISA, in addition to measurement of biochemical parameters such as renal function tests (urea, creatinine), liver function tests (albumin, ALT, AST), and electrolyte levels such as sodium, potassium, and chloride. Results: The study showed that patients with chronic HBV had significantly higher levels of urea and creatinine compared to the control group, indicating that their renal function was affected. Low levels of albumin and increased liver enzymes were also observed, reflecting the presence of possible liver damage associated with hepatitis B. Conclusions: This study confirms the existence of an association between chronic hepatitis B and deterioration in renal function. Therefore, it is recommended to conduct periodic follow-up of renal function in HBV patients to detect any potential complications early and take the necessary therapeutic measures.